Dual responsive cellulose microspheres with high solid-state fluorescence emission - Yadav, Prashant; Prajitha, K. P.; Dhaware, Vinita; Subramani, Mohan; Joy, Pattayil; Asha, S. K.; Shanmuganathan, Kadhiravan (Colloids and Surfaces A-Physicochemical and Engineering Aspects, 2020)
Materials that respond to multiple stimuli such as magnetic field and light are attractive for security and medical diagnostic applications. One of the major challenges in dual functional microspheres is that the presence of magnetic nanoparticles can quench fluorescence emission. Also, there is a probability of solid-state quenching due to the proximity of the fluorophore. We report here a facile approach to prepare cellulose microspheres with high solid-state fluorescence using 40 % tetrabutylammonium hydroxide (TBAH). The fluorescence quenching effect due to the presence of Fe3O4 nanoparticles and solid-state quenching due to aggregation of fluorophore was systematically investigated. Microspheres with the detectable magnetic response and fluorescence quantum yield as high as 0.57 (FMB 414) was obtained by optimizing the reaction conditions. Such a high quantum yield has not been reported before for dual stimuli-responsive fluorescent microspheres. The magnetic and fluorescent properties were found to be durable even after multiple washing cycles. These dual responsive cellulose microspheres can be added as security features to authenticate documents such as passports, degree certificates, currency notes, financial documents etc.
Keywords: Fluorescent; Magnetic; Microcrystalline cellulose; microspheres; Stimuli responsive microspheres; Tetrabutylammonium hydroxide

Magnetism in bimetallic NiII-CoII coordination polymer - Gupta, Kriti; Dadwal, Arun; Joy, Pattayil; Ballav, Nirmalya (AIP Conference Proceedings, 2020)
Co-BDC ([Co2(OH)2BDC], H2BDC = 1,4-benzenedicarboxylic acid) is known to possess metamagnetism originating from the antiparallel spins and high magneto crystalline anisotropy of Co(II).1 Herein, we have introduced a bimetallic concept by incorporating Ni(II) along with Co(II) in the same coordination polymer to modulate the magneto crystalline anisotropy in the lattice which in turn, affects the overall magnetic response of the coordination polymer. The Curie-Weiss equation fit suggested antiparallel arrangement of the spins (θ ≈ -62.5 K) of Ni(II) and Co(II) arranged in alternate fashion. The cusp in magnetization was observed at 7 K (Tc) with a significant coercive field of ∼750 Oe at 5 K.